Effects of Abiotic Stresses on the Growth of Vagina radiate - Mah, Choon Bin (2016)
Abiotic stresses are discouraging the normal growth and production of crops. Unlike animals, plants which do not have the motile system are unable to escape from this disaster. Hence, this experiment was to determine the effects of abiotic stresses (osmotic stress, salinity and heavy metal stress) on the growth of Vigna radiate. In this study, the seeds of V. radiate were cultured onto black soil supplemented with Murashige and Skoog (MS) medium which served as control or MS medium anugmented with various concentrations of abscisic acid (ABA) (1 mg/L, 2 mg/L, 5 mg/L, 10 mg/L, 15 mg/L and 20 mg/L), sodium chloride (NaCI) (1 mg/L, 5 mg/L, 10 mg/L, 20 mg/L, 30mg/L and 40 mg/L). The number of leaves and stem height of V. radiate were observed and recorded over a period of 22 days. Under the treatment of ABA, the leaves turned from green to yellow and eventually withered. The highest mean number of leaves was 2 per explant at 1 mg/L, 2 mg/L, 5 mg/L and 15 mg/L ABA. The highest mean stem height was 21.058 cm at 2 mg/L ABA. On the other hand, NaCI stress resulted in the formation of dried leaves. The peak average number of leaves was 2 per explant at 1 mg/L and 5 mg/L of NaCI while the peak of average stem height was 17.15 cm at 1 mg/L NaCI. Cd showed its effect by turning the greenish leaves into yellowish and the leaves became soft. The optimal mean of amount of leaves was 2 at all concentrations tested while 0.00050 mg/L of Cd yielded the optimal average of stem height, which was 18.85 cm. Leaf chlorosis was also observed in the Cd treatment. In a nutshell, the abiotic stresses (ABA, NaCI, Cd) utilized in this study was proven to impose their negative effects on the growth of V. radiate.